Locomotion Variations of Arch Index and Interlimb Symmetry in Shod and Barefoot Populations - Peimin Yu; Minjun Liang; Feng Ren (Applied Bionics and Biomechanics)
The purpose of this study was to investigate the variations of arch index from static standing to dynamic walking and running; furthermore, the interlimb symmetry was checked in the two populations. A total of eighty male participants were recruited for this study, with forty habitually barefoot and forty habitually shod males, respectively. Arch index (AI) was calculated following the previously established “gold standard” measurement via contact areas recorded from EMED. Repeated measure analysis of variance (ANOVA) was employed to compare the difference between static and dynamic walking and running arch index. Paired-samples t-test and symmetry index (SI) were used to investigate the symmetry of the left foot arch index and right foot arch index. It was found that the dynamic arch index was significantly higher than the static arch index in barefoot and shod males, showing an increase from static weight-bearing standing to dynamic walking and running. However, interlimb (right-left) symmetry in the foot arch index was observed in the two populations. Dynamic changes of the arch index may provide implications that need to be considered while designing shoe lasts or insoles. Knowledge of the healthy arch index range reported from this study could also be used as a standard baseline to probe into foot and arch disorders.